eTechnology. The basics of relational databases using MySQL. - Blansit BD (Journal of Electronic Resources in Medical Libraries, 2006)
Going beyond a simple database table, a relational database fits more complicated systems by relating information from two or more database tables. This paper will use MySQL to develop a basic appreciation of relational databases including user administration, database design, and SQL syntax. It will lead the reader in downloading and installing MySQL, planning a database, building that database, adding data to the database, and some simple manipulation of that data.